The discipline of Geography and the use of pedagogical games as a methodological teaching resource: an experience with 9th grade and PG IV - Roselma Lopes Ribeiro (Universidade Estadual de Alagoas, 2020)
The present work approaches the use of pedagogical games as a methodological resource in the teaching of Geography. The objective is to present the methodological resources used inthe classroom in the discipline of Geography. The activities were developedin the 9th grade classes of Elementary School II and in the class of PG IV during the Institutional Program of Teaching Initiation Scholarship (PIBID) in a state school in the city of Maceió / AL. The games used as a methodological resource in the classroom were geographic bingo and word search. Thus, providing students with a playful and motivating learning focused on the development of cognitive skills such as observation, interaction and participation in the proposed activities.